The immediate and short-term impact of COVID 19 infections on nurses in a UAE hospital - Khaled Al Qawasmeh; Nabeel Al Amiri; Salma Omar Al Nuaimi (BMC, 2022)
Abstract Background/Aims Nurses were on the front line against the COVID 19 pandemic, fighting to save human lives. Many nurses sacrificed their well-being and social life to win the battle. In consequence, many nurses have been infected with the virus around the Globe. This study aims to determine the immediate and short-term physical, psychological, and social impact of COVID 19 infection on nurses and midwives retrospectively. On the other hand, it aims to find the effect of COVID 19 stigma on the self-esteem of the infected nurses. Methods To achieve this goal, the authors used an exploratory, mixed-method design with a sample of nurses and midwives working in a tertiary hospital in UAE who has been infected with the COVID 19 virus and recovered. The authors have used the qualitative results to explain and interpret the findings of the quantitative findings. The data were collected through distributing the quantitative survey to participants and then it was followed by conducting semi-structured interviews. Results The careful exploration of the experiences of nurses infected with the COVID 19 virus suggested a simple model that manages the patients in hospitals and at homes, including improving self-efficacy and patient coping, providing the basic nursing skills to patients and families, providing continuous psychological support, and providing high standards of health care. Conclusion The new suggested model will maintain a positive status of wellbeing amongst infected patients during the infection time and in 3-6 months after the infection.